PUSH FACTOR AND PULL FACTOR ANALYSIS ON ECONOMIC GROWTH THROUGH CAPITAL FLOWS IN INDONESIA - Aprella, Revi; Endang NP, Maria Goretti Wi; Darmawan, Ari (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2025)
Purpose The purpose of this research is to find out how domestic conditions (pull) and external conditions, especially the economic conditions of the United States (push factor) towards capital flows, where the increasing in capital will affect economic growth in Indonesia. Design/methodology/approach The method used in this study is PLS (Partial Least Square) using WarpPLS. The study used 4 (four) variables: push factor, pull factor, capital flow and economic growth. This research is an explanatory research with a quantitative descriptive approach. The data source for this research comes from World Bank, Federal Reserve, IMF. Findings The results show a significant negative relationship between push factors and both capital flows and economic growth, as well as between pull factors and economic growth.. There is a negative statistically insignificant relationship between pull factors and capital flows, and between capital flows and economic growth. Capital flows are not able to mediate the push effect factors on economic growth and the pull effect factors on economic growth. Research limitations/implications This study has several limitations such as limited data and the research was only conducted in Indonesia which may limit generalizability to other countries or regions. Originality/value This study offers a comprehensive understanding of the influence of push and pull factors on economic growth via capital flows in Indonesia, which may support the formulation of macroeconomic policy.